Does benign prostate hyperplasia histopathological variation impact disease‐specific clinical outcomes after transurethral resection?. Issue 4 (3rd February 2023) - Berk, Brittany; Acosta, Andres; Ernandez, John; Dey, Tanujit; Kathrins, Martin
Abstract: The impact of histopathological variants in stromal and glandular tissue on clinical outcomes following transurethral resection of prostate (TURP) is unexplored. We sought to evaluate the relationship between histopathological variations in TURP specimen and postoperative clinical outcomes. We performed a retrospective analysis of men undergoing initial TURP at our institution from 2017 to 2019. All pathology slides were re‐reviewed by one specialized genitourinary pathologist who was blinded to all clinical data. Types of BPH were defined as: glandular‐predominant (gland:stroma ratio >50%), mixed (gland:stroma ratio 25%–50%), and stromal‐predominant (gland:stromal ratio <25%). Primary clinical outcomes were ∆ post‐void residual and ∆ American Urological Society Symptom Score (AUASS) at 3, 6, and 12 months post‐operatively. We also evaluated for a temporal relationship between time since surgery and ∆AUASS amongst different histopathological subgroups. One hundred and five patients were included in the final analysis. 61/105 (58.1%) had glandular‐predominant histopathology, 21/105 (20%) had stromal‐predominant histopathology, and 23/105 (21.9%) were classified as mixed histopathology. On univariate and multivariate analysis, histopathological subtype was not a significant predictor of any of the clinical post‐operative endpoints of interest at any time points. Disease‐specific outcomes after TURP appear to be consistent across these different histopathologic subtypes.